1994
DOI: 10.1149/1.2059261
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Atmospheric Corrosion of Copper in the Presence of Submicron Ammonium Sulfate Particles at 300 and 373 K

Abstract: The corrosion mechanism of copper at 373 and 300 K in the presence of submieron (NH~)2SO4 particle deposits has been investigated. Several in situ techniques have been used to monitor the corrosion process in real time. At and above the critical relative humidity of (NH4)2SO4, dissolution of Cu is followed by formation of Cu20, oxidation of Cu(I) ions to Cu (II) ions, and precipitation of antlerite [Cu3(SO4)(OH)4], broehantite [Cu4(SO4)(OH)6], or posnjakite [Cu4(SQ)(OH)~ -HzO]. The amount of corrosion product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 4 publications
4
36
0
Order By: Relevance
“…Weak band at 1632 cm −1 is OH deformation vibration. The band characteristic of cupric sulfate [65] is also observed around 1110 cm −1 . The absorption band at 625 cm −1 [66] is assigned to cuprite (Cu 2 O).…”
Section: Ftir Spectroscopymentioning
confidence: 84%
“…Weak band at 1632 cm −1 is OH deformation vibration. The band characteristic of cupric sulfate [65] is also observed around 1110 cm −1 . The absorption band at 625 cm −1 [66] is assigned to cuprite (Cu 2 O).…”
Section: Ftir Spectroscopymentioning
confidence: 84%
“…The aerosol's chemistry affects its potential corrosiveness (Lau et al 2008;Wan et al 2002;Lobnig et al 1994) and determines the values of DRH and CRH (Martin 2000;Martin et al 2003;Seinfeld and Pandis 1998;Potukuchi and Wexler 1995). Thus, the second half of the PM 2.5 samples used in the AEC was chemically analysed to determine the aerosol chemical composition.…”
Section: Aerosol Chemical Characterizationmentioning
confidence: 99%
“…(Shehabi et al 2008). If aerosol deposits on electronic circuitry and the ambient RH exceeds the aerosol DRH, or remains higher than the aerosol CRH (while decreasing from above the DRH), the water-soluble ionic compounds are dissociated and the aerosol is then electrically conductive and corrosive (Song et al 2013;Shehabi et al 2008;Tencer 2008;Syed 2006;Yang et al 2006;Lobnig et al 1994). This behaviour constitutes a serious risk in DCs because, as Leiva et al (2013) have shown, atmospheric pollution is often related with high concentrations of water-soluble inorganic ions.…”
Section: Introductionmentioning
confidence: 99%
“…The atmospheric corrosion of copper has been studied extensively due to the vast use of this metal in many engineering applications including the electrical-electronic industry [1][2][3][4]. Copper corrosion products formed during field exposure have been analyzed using several techniques, including X-ray Photoelectron Spectroscopy (XPS), Infrared Reflection Absorption Spectroscopy (IRAS), Auger Electron Spectroscopy (AES) and X-ray Diffraction (XRD) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%